Recurrent seizures after lidocaine ingestion - Hamed Aminiahidashti; Abolghasem Laali; Nazanin Nosrati; Fatemeh Jahani (Wolters Kluwer Medknow Publications, 2015)
Lidocaine has a concentration-dependent effect on seizures. Concentrations above 15 μg/mL frequently result in seizures in laboratory animals and human. We report a case of central nervous system (CNS) lidocaine toxicity and recurrent seizure after erroneous ingestion of lidocaine solution. A 4-year-old boy presented to the Emergency Department of Imam Hospital of Sari in December 2013 due to tonic-clonic generalized seizures approximately 30 min ago. 3 h before seizure, his mother gave him 2 spoons (amount 20-25 cc) lidocaine hydrochloride 2% solution instead of pediatric gripe by mistake. Seizure with generalized tonic-clonic occurred 3 times in home. Neurological examination was essentially unremarkable except for the depressed level of consciousness. Personal and medical history was unremarkable. There was no evidence of intracranial ischemic or hemorrhagic lesions in computed tomography scan. There were no further seizures, the condition of the patient remained stable, and he was discharged 2 days after admission. The use of viscous lidocaine may result in cardiovascular and CNS toxicity, particularly in children. Conservative management is the best option for treatment of lidocaine induced seizure.